Effects by Various Cross Sections on Monoshocks Helical Spring Using Static Stress Analysis and Sustainable Analysis - ., Ganeshan; ., Kamalakannan; ., Sivakumar; koon Tatt, Tan; ., Kasirajan (International Journal of Engineering and Technology, 2019)
Mono suspension system installed in two-wheeler vehicles is to absorb impulsive shock loads caused often by irregular jumpy road surfaces. The shock impulsive force by the jumps is absorbed by the mono-suspension system through wheel. To provide comfort ride over rough surface, the suspension system should be equipped in. The core objective of the suspension system is to provide good comfort and better ride control to the riders. The perspective of this research is to conduct von mises stress analysis and displacement analysis on mono shocks helical spring to optimize the weight of the helical spring without affecting its functional requirements. To optimize the weight of the mono-suspension helical spring, various cross sections for helical spring design is used and von mises stress analysis and displacement analysis on each cross section has to be done to compare the weight, stress capability and maximum displacement. These two analyses are carried out by solid works simulation Xpress module. Theses analyses helps to recommend better cross section should be used to make helical spring mono-shocks with optimized weight and without affecting its functional requirements and environmental impact.Â Â Â